Trello - Johnson, MLIS, Heather A. (Journal of the Medical Library Association, 2017)
Trello, a cloud-based tool that uses the Kanban method of project management. With Trello, users can visually organize projects into boards, divide projects into groups, and subdivide groups into tasks.